Effect of inoculation and time of application of microbes on growth and yield of soybean (Glycine max (L.) Merrill) - S Muslikah; S Sudiarso; L Setyobudi (Brawijaya University, 2016)
The application of inorganic fertilizers continuously can result in hardening of soil, narrowing of soil pores, thus the roots will have difficulty in penetrating soil. Biological properties of soil that decreases could lead to disruption of microorganism activity, so that the decomposition of organic matter of soil become obstructedand soil fertility decline. Therefore, it is advisable to use an alternative to application of microbes, i.e. Rhizobium and effective microorganisms 4 (EM4) that will enhance the availability of nutrients for plants. This study was aimed to determine the effect of inoculation and time of application of the microbes on the growth and yield of soybean. The experiment was conducted in the greenhouse located 500 m above sea level. The design used for the experiment was a completely randomized design with three replications. Observations of non-destructive and destructive data were analyzed by analysis of variance (F test) at 5% level and continued with LSD at 5% level. The results showed significant effect treatments applied on the growth and yield components. Treatment i6 (EM4 applied at 1 week after planting) was the best treatment, as shown by the increased number of pods by 95.94%, dry weight of pods by 38.25%, total dry matter, seed by 24.61%, and 68.40% weight of 100 seeds.